1989
DOI: 10.1111/j.1365-2141.1989.tb06277.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and causes of death in Dutch haemophiliacs, 1973–86

Abstract: Summary. Mortality figures were calculated for a group of 717 Dutch haemophiliacs over the period 1973-86. Followup was on average 10-9 years; no patients were lost to followup. The data were compared to the general male population by actuarial methods and patient-year analysis. Forty-three patients died, while 20 deaths were expected in a hypothetical group of non-haemophiliacs of the same age distribution. Hence, overall mortality was 2·l times higher than in the general population. This leads to a calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
186
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(197 citation statements)
references
References 20 publications
(21 reference statements)
8
186
1
Order By: Relevance
“…Several European studies [1][2][3] and one U.S. study [4] of cause-specific mortality have found lower rates of death from ischemic heart disease in persons with hemophilia compared to the general population. These findings have been interpreted as providing evidence that the hypocoagulable state offers protection from the thrombotic event that precipitates infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Several European studies [1][2][3] and one U.S. study [4] of cause-specific mortality have found lower rates of death from ischemic heart disease in persons with hemophilia compared to the general population. These findings have been interpreted as providing evidence that the hypocoagulable state offers protection from the thrombotic event that precipitates infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Since then nationwide surveys were repeated in 1978,1985,1992 and in 2001 [21][22][23][24]. These studies aimed at assessing the medical and social consequences of haemophilia in the Netherlands.…”
Section: Settingmentioning
confidence: 99%
“…The mean age of patients differed according to severity of haemophilia and HCV status; patients with severe haemophilia, who were never infected, were younger [mean age 23 years, 95% confidence interval (CI) [19][20][21][22][23][24][25][26][27][28] …”
Section: Hepatitis Cmentioning
confidence: 99%
“…In 1986, thanks to the introduction of virally safe coagulation concentrates by the implementation of virucidal methods in the manufacturing process, individuals in the hemophilia community once again began to hope for a long, healthy, and active life. [6][7][8] Nowadays, given the improvement in coagulation concentrates, the life expectancy of individuals with hemophilia appears to be equal to that of individuals without hemophilia in developed countries. [9][10][11] Furthermore, recent findings have demonstrated that prophylaxis regimens decrease bleeding, pain, the frequency and duration of hospitalizations, disability, and quality of life in the hemophiliac population.…”
Section: Introductionmentioning
confidence: 99%